PENGEMBANGAN MODUL BERBASIS FIELD TRIP UNTUK KEMAMPUAN EKOLITERASI SISWA DALAM PEMBELAJARAN IPS MATERI KENAMPAKAN ALAM KELAS V - Aulia, Corry Rahma; Hanifah, Nurdinah; Karlina, Dety Amelia (Universitas Negeri Medan, 2025)
The research aims to develop a field trip-based module for students' ecoliteracy skills in social studies learning natural appearance material for class V. This research uses the Research and Development (RnD) method with the ADDIE development model. The subjects in this research were 3 teachers and 21 class V students at SDN 9 Sijuk. The instruments used in this research include observation sheets, validation questionnaires, teacher response questionnaires and student responses. The field trip-based module has been validated by material experts with a percentage of 90%, module experts at 95%, media experts at 93%, language experts at 100% and the conclusion was that the module is in the very feasible category. The implementation results received a positive response from teacher assessments with an average percentage of 95% and student responses with an average of 94%. It can be concluded that the module developed is suitable for use in social studies learning in class V and can be used by students both at school and outside school.